1990
DOI: 10.1254/jjp.52.101
|View full text |Cite
|
Sign up to set email alerts
|

Action sites of antiallergic drugs on human neutrophils.

Abstract: Abstract-Sites of the inhibitory action of antiallergic drugs (azelastine, oxatomide, tranilast, repirinast and amlexanox) on human neutrophils were investigated by measuring leukotriene B4 formation, arachidonic acid release and superoxide generation. Results obtained in this study were as follows: (1) Formations of leukotriene B4 by neutrophils activated with a calcium ionophore (A23187) were effectively inhibited by all types of antiallergic drugs examined here, although the required concentrations were wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Taniguchi et al (13,14) have previously reported that azelastine inhib its the amount of 02 generated by neutro phils, and this was confirmed by the results of the present investigation. In addition, our re sults show that the drug reduced the amount of H202 and OH generation by neutrophils, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Taniguchi et al (13,14) have previously reported that azelastine inhib its the amount of 02 generated by neutro phils, and this was confirmed by the results of the present investigation. In addition, our re sults show that the drug reduced the amount of H202 and OH generation by neutrophils, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, 02 gen eration by phorbol 12-myristate 13-acetate (PMA)-stimulated neutrophils is also reduced in the presence of the drug (14). These reports seem to indicate that azelastine may inhibit the process of phospholipase A2 activation and/or the mobilization of calcium from the intracellular storage sites.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unfortunately the above drugs were either only partially effective in our patient or could not be used at all. Accordingly we focused on colchicine's characteristic function of inhibiting neutrophil chemotactic activity (12) and found that the anti-allergic drug azelastine also inhibits neutrophil chemotaxis (13). Azelastine, like colchicine, successfully reduced the frequency and degree of the attacks in the present patient.…”
Section: Discussionmentioning
confidence: 70%
“…Accordingly we needed to seek another treatment and focused on colchicine's characteristic function: inhibition of neutrophil chemotactic activity (12). We searched for another drug having a similar function and found that azelastine, which is an anti-allergic drug, also inhibits neutrophil chemotaxis (13). We have since been administering 4-6 mg of azelastine to her daily and her attacks of fever and polyserositis have decreased.…”
Section: Case Reportmentioning
confidence: 99%